The effects of molecular weight and thermal decomposition on the sensitivity of a thermal desorption aerosol mass spectrometer. Issue 2 (1st February 2016) - Murphy, D. M.
ABSTRACT: In free molecular flow the slower speed of heavier molecules means that they spend more time in the ion source of a mass spectrometer. Hence the sensitivity of the thermal desorption mass spectrometers such as the Aerodyne Aerosol Mass Spectrometer (AMS) should include a term that scales as the square root of the molecular weight. Thermal decomposition on the vaporizer reduces the molecular weight prior to ionization and changes electron impact cross-sections. Thermal decomposition therefore has the potential to change the sensitivity, in some cases by more than a factor of three. Current AMS calibrations that rely upon an ammonium nitrate calibration and scaling for other components with a relative ionization efficiency may overestimate the concentration of large, thermally stable molecules and underestimate small or thermally unstable molecules. The overall sensitivity of the AMS to organics includes a partial cancellation of these effects. There is an incomplete understanding of the vaporization process, including that of ammonium nitrate.